Hibernating Myocardium and Role of 18F FDG PET Cardiac Imaging – A review - Hussain, Raihan (Bangladesh Journal of Nuclear Medicine, 2018)
The term “Hibernation” is a challenging term but not infrequently used in Nuclear Cardiology. It often is used synonymously for tissue viability, although technically there are some differences. Viability is a prospective definition, but it does not imply evidence of functional recovery after interventions whereas hibernation is a retrospective definition based on evidence of functional recovery after interventions. But for practical clinical purposes both carries the similar meaning. The aim of this review article is to summarize our current understanding of the concept of hibernation and its clinical implications in patients with coronary artery disease (CAD) and the role of FDG PET study in its proper evaluation. Bangladesh J. Nuclear Med. 20(1): 45-50, January 2017